Glow discharge plasma switch controlled by a small magnetic field - Rocca, Jorge J., author; Floyd, K., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1992)
A cold plasma switch scheme with opening and closing capabilities is reported. An externally applied magnetic field causes a low pressure hollow cathode discharge to transition from a low impedance mode sustained by oscillating beam electrons into a virtually collisionless high impedance mode. The impedance of a 10 A discharge was demonstrated to increase by 20 with the application of a field of 0.018 T.